2014
DOI: 10.1186/1472-6874-14-43
|View full text |Cite
|
Sign up to set email alerts
|

Highly-cited estimates of the cumulative incidence and recurrence of vulvovaginal candidiasis are inadequately documented

Abstract: BackgroundAvailable literature concerning the epidemiologic or clinical features of vulvovaginal candidiasis commonly reports that: 75% of women will experience an episode of vulvovaginal candidiasis in their lifetimes, 50% of whom will experience at least a second episode, and 5-10% of all women will experience recurrent vulvovaginal candidiasis (≥4 episodes/1 year). In this debate we traced the three commonly cited statistics to their presumed origins.DiscussionIt is apparent that these figures were inadequa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 69 publications
3
29
0
Order By: Relevance
“…is affected by the immune status of the host, lower body resistance, pH changes in the vagina, lifestyle, abuse of antibiotics and pregnancy (10, 11). In our study, the overall positivity rate of Candida infection was 22.45%, of which C. albicans was the main species identified.…”
Section: Discussionmentioning
confidence: 99%
“…is affected by the immune status of the host, lower body resistance, pH changes in the vagina, lifestyle, abuse of antibiotics and pregnancy (10, 11). In our study, the overall positivity rate of Candida infection was 22.45%, of which C. albicans was the main species identified.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent attacks of vulvovaginal candidiasis have been estimated to affect 5-10% of women annually [58,59], primarily based on data from Foxman et al [36,37] (Table 2). Estimates of rVVC are intrinsically difficult to conduct to reliably estimate the incidence and prevalence of rVVC among women [59].There are no reports of rVVC from East Africa, but a study in Tunisia found a similar prevalence of 6.1% [60].…”
Section: Candida Infectionsmentioning
confidence: 99%
“…(4,5) This is firstly a consequence of the widespread availability of over the counter (OTC) antifungal agents. Procurement of the easily available, numerous highly effective topical antimycotic agents, although controversial, can be considered a boon to womens health.…”
Section: Introductionmentioning
confidence: 99%